2021
DOI: 10.1371/journal.ppat.1009376
|View full text |Cite
|
Sign up to set email alerts
|

A systematic analysis of hypermucoviscosity and capsule reveals distinct and overlapping genes that impact Klebsiella pneumoniae fitness

Abstract: Hypervirulent K. pneumoniae (hvKp) is a distinct pathotype that causes invasive community-acquired infections in healthy individuals. Hypermucoviscosity (hmv) is a major phenotype associated with hvKp characterized by copious capsule production and poor sedimentation. Dissecting the individual functions of CPS production and hmv in hvKp has been hindered by the conflation of these two properties. Although hmv requires capsular polysaccharide (CPS) biosynthesis, other cellular factors may also be required and s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
108
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 85 publications
(135 citation statements)
references
References 65 publications
13
108
2
Order By: Relevance
“…A total of eight variants were shared in all isolates from Italy but missing in all Middle East genomes (node 1). Of particular interest were 1) a predicted LOF mutation in cycA which encodes a serine/alanine transporter that, when functional, allows the antibiotic d -cycloserine to cross the cell wall and reach its cytoplasmic target ( 26 ), 2) an NSY mutation in pabA involved in aromatic amino acid biosynthesis and previously characterized as a general infection requirement for K. pneumoniae ( 27 ), and 3) an NSY mutation in hdfR encoding for a transcriptional regulator involved in the complex regulation of capsule production and hypermucoviscosity ( 28 ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of eight variants were shared in all isolates from Italy but missing in all Middle East genomes (node 1). Of particular interest were 1) a predicted LOF mutation in cycA which encodes a serine/alanine transporter that, when functional, allows the antibiotic d -cycloserine to cross the cell wall and reach its cytoplasmic target ( 26 ), 2) an NSY mutation in pabA involved in aromatic amino acid biosynthesis and previously characterized as a general infection requirement for K. pneumoniae ( 27 ), and 3) an NSY mutation in hdfR encoding for a transcriptional regulator involved in the complex regulation of capsule production and hypermucoviscosity ( 28 ).…”
Section: Resultsmentioning
confidence: 99%
“…2c ). Note that while many genes are required for full capsule production or hypermucoidy in K. pneumoniae ATCC 43816 and its derivative K. pneumoniae KPPR1 ( 30 , 36 ), only those genes where mutation is predicted to result in a complete loss of capsule were required for RAD2 infection. To validate the role of the capsule for RAD2 infection, an acapsular mutant of B5055 which lacks wzb and wzc was used as an infection host ( 37 ).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, our results indicate that the K1 genotype, rmpA , and aerobactin are substantial predictors of hvKp infection. Each of these virulence factors may affect pathogenesis independently but in a coordinated manner; a recent study suggested that capsule biosynthesis, hypermucoviscosity, and metabolism coordinately affect K. pneumoniae fitness [ 23 ]. Conversely, a positive string test was inferior to these predictors and was less accurate for identifying hvKp (sensitivity of 84.2%, specificity of 43.3%, and positive LR of 1.49 [95% CI: 0.99–1.79]) than reported previously (sensitivity of 89% and specificity of 91%) [ 2 ].…”
Section: Discussionmentioning
confidence: 99%